2008
DOI: 10.4161/auto.6309
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy delays apoptosis in renal tubular epithelial cells in cisplatin cytotoxicity

Abstract: One of the major side effects of cisplatin chemotherapy is toxic acute kidney injury due to preferential accumulation of cisplatin in renal proximal tubule epithelial cells and the subsequent injury to these cells. Apoptosis is known as a major mechanism of cisplatin-induced cell death in renal tubular cells. We have also recently demonstrated that autophagy induction is an immediate response of renal tubular epithelial cell exposure to cisplatin. Inhibition of cisplatin-induced autophagy blocks the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
95
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 25 publications
5
95
1
Order By: Relevance
“…We observed that autophagy was enhanced by etoposide. The upregulation of autophagy by chemotherapeutic drugs has already been described [42][43][44][45][46][47]. Chemotherapyinduced autophagy may promote cell resistance against it.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We observed that autophagy was enhanced by etoposide. The upregulation of autophagy by chemotherapeutic drugs has already been described [42][43][44][45][46][47]. Chemotherapyinduced autophagy may promote cell resistance against it.…”
Section: Discussionmentioning
confidence: 92%
“…Doxorubicin-induced DNA damage stimulates cytoprotective autophagy through a PARP-1-dependent pathway [48]. Similarly, cisplatin-induced autophagy delays apoptosis in renal tubular epithelial cells [45] and tamoxifen and camptothecin-induced autophagy increases MCF7 breast carcinoma cell line viability [42,46]. Examples of autophagic cell death in response to chemotherapy were also described.…”
Section: Discussionmentioning
confidence: 98%
“…In certain in vitro models, inhibition of autophagy increased cell death after injury whereas in others cell death was decreased. 12,13,22,28,32 It is recognized however that autophagy is induced during stress, and when stress persists, it may converge into apoptotic pathways. 30,31 This dual nature of autophagy and the increasing number of pathologies it is associated with highlight the importance of studying the regulation and effects of autophagy during kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,18,22,27 Under normal physiologic conditions, cells use autophagy to maintain homeostasis. If insufficient autophagy occurs, long-lived proteins and damaged organelles accumulate and cell death occurs.…”
mentioning
confidence: 99%
See 1 more Smart Citation